Transfer function asymmetry in Fabry-Perot-based optical pressure sensors - Czuchnowski, Jakub; Prevedel, Robert (Optics letters, 2022)
Optical resonators are some of the most promising optical devices for manufacturing high-performance pressure sensors for photoacoustic imaging. Among these, Fabry-Perot (FP)-based pressure sensors have been successfully used for a multitude of applications. However, critical performance aspects of FP-based pressure sensors have not been studied extensively, including the effects that system parameters such as beam diameter and cavity misalignment have on transfer function shape. Here, we discuss the possible origins of the transfer function asymmetry, ways to correctly estimate the FP pressure sensitivity under practical experimental conditions, as well as show the importance of proper assessments for real-world applications.